The Government’s Role in the Development of Yendi Beach Tourism Destinations in Biak Numfor Regency - Djamil Hasyim; Amiruddin Gunawan; Moh Sudi; Delly Mustafa; Rijal Rijal (Jurnal Ad'ministrare, 2019)
Tourism is a magnet of a region to realise a developing area. This study aims to clarify the role of the Government in the Development of Yendi Beach Tourist Attraction in Biak Numfor Regency. This research uses a descriptive qualitative approach. Data collection techniques are done through observation, interviews, literature studies, and documentation. The results showed that the role of the Tourism Office in developing Yendi Beach's tourism potential in Biak Numfor District was dominant as a Motivator compared to other roles, namely as a Facilitator and a Dynamicsator. This role as a facilitator is seen mainly in the form of: provision of facilities and infrastructure for tourist attraction objects, which are still largely borne by the Department of Tourism as the leading sector, facilitation in channelling stimulant financial assistance for people who want to develop tourism attractions, promotion of attraction objects tourism, as well as facilitation to third parties, such as investors and tourism entrepreneurs to develop Yendi Beach tourism business in Biak Numfor Regency.